PERLINDUNGAN HUKUM TERHADAP KORBAN KEJAHATAN SIBER DALAM SISTEM PERADILAN PIDANA INDONESIA - Medi Islamta Sembiring; Suci Ramdani; Meina Alvionita Br Purba; Lume Hetty Alphani Simbolon (CV. Lafadz Jaya, 2026)
The development of information and communication technology has had a positive impact on various aspects of society. However, these technological advancements have also given rise to various forms of cybercrime, causing significant losses to individuals and communities. Victims of cybercrime often suffer not only financial losses but also non-material damages, including violations of their privacy rights and personal data security. This study aims to analyze the legal framework governing the protection of cybercrime victims within the Indonesian criminal justice system, examine its implementation, and identify the obstacles encountered in providing legal protection to victims. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that legal protection for victims of cybercrime has been regulated under several laws and regulations, including the Law on Electronic Information and Transactions, the Personal Data Protection Law, and the Law on the Protection of Witnesses and Victims. Nevertheless, the implementation of these legal provisions remains inadequate due to several challenges, such as the limited capacity of law enforcement officers, difficulties in identifying perpetrators, and the transnational nature of cybercrime. Therefore, strengthening the legal framework, enhancing the capacity of law enforcement agencies, and optimizing the protection of the rights of cybercrime victims are essential to improving legal protection within the Indonesian criminal justice system.